Efectos del Estado como poder del Estado: expectativa, ansiedad y temor en la cuenca media del Inambari - Lewis Denegri, Francisco (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
This ethnography examines the (re)production of the Peruvian state’s power in the fabric of the everyday in the Inambari valley, located in Puno. I argue that focusing on both real and imaginary ‘State-effects’ provides us with a way of tracing the Peruvian state’s power in this context. Further, I examine the social effects of the convergence of two infrastructural projects, both geared towards global, neo-liberal integration, arguing that this convergence led to the creation of a social milieu fraught with feelings of expectation, anxiety, optimism and fear.

En esta etnografía se examina la (re)producción del poder del Estado peruano en el tejido de la vida cotidiana en la cuenca media del Inambari, Puno. Propongo que el enfoque en los llamados «efectos del Estado», tanto reales como imaginarios, permite localizar e identificar el poder del Estado peruano en este contexto. Por otro lado, se exploran los efectos sociales de la convergencia de dos proyectos de infraestructura que son a su vez producto de la integración del Perú en la economía global neoliberal, y planteo que dicha convergencia genera un entorno social plagado de expectativas, ansiedad, optimismo y miedo
State-effects as state power: Expectation, anxiety and fear in the Inambari valley
Keywords: Estado; Infraestructura; Emociones; Medio ambiente; Cotidianeidad; https://purl.org/pe-repo/ocde/ford#5.04.03